Implementation of Strategik Management, Human Resources for the Increase Perfomance in State Owned Corporation Enterprises (SOES) in Indonesia - Kusumawati, Indah; Yulistiyono, Agus; Badrianto, Yuan (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2022)
This study aims to determine the dominan factors in implementation of strategic management for the increase performance in S0E,s Indonesia . The study was conducted in organization company with my country Indonesia, in state owned corporation (S0E’s) will make Soe more transparent reliability between clean soe with land agencies Soe’s prosecutors of state owned . Definition S0E’s UU No.19. 2003 years S0E’s source of wealth the country for the prosperity Indonesia people The description of S0E’s so far has not been in line with what is expected to still be a lot of politicization and birocraci managing’s, this can still be seen from the low level of profitability, not market-oriented, low quality , productivity, and results of performance need to be improved, to improve performance and productivity then there is a need for strategic management in order to improve the performance of towards a better direction. This is influenced by human resources, strategic management, and performance organizations